Targeted next-generation sequencing identifies novel variants in candidate genes for Parkinson’s disease in Black South African and Nigerian patients - Oluwole, OG; Kuivaniemi, H; Abrahams, S; Haylett, WL; Vorster, AA; van Heerden, CJ; Kenyon, CP; Tabb, DL; Fawale, MB; Sunmonu, TA; Ajose, A; Olaogun, MO; et al. (BioMed Central, 2020)
Background: The prevalence of Parkinson’s disease (PD) is increasing in sub-Saharan Africa, but little is known about the genetics of PD in these populations. Due to their unique ancestry and diversity, sub-Saharan African populations have the potential to reveal novel insights into the pathobiology of PD. In this study, we aimed to characterise the genetic variation in known and novel PD genes in a group of Black South African and Nigerian patients.